How to Choose the Correct Drug in Severe Pediatric Asthma - Bush, Andrew (Frontiers in Pediatrics, 2022)
When a child with severe asthma (defined clinically for the purposes of this review as wheeze, breathlessness, chest tightness sometimes with cough) does not respond to treatment it is important to be sure that an alternative or additional diagnosis is not being missed. In school age children, the next step is a detailed protocolized assessment to determine the nature of the problem, whether within the airway or related to co-morbidities or social/environmental factors, in order to personalise treatment. For example, those with refractory difficult asthma due to persistent non-adherence may benefit from using budesonide and formoterol combined in a single inhaler (SMART) as both reliever and preventer. For those with steroid-resistant Type 2 airway inflammation the use of biologicals such as omalizumab and mepolizumab should be considered, but for mepolizumab at least there is a paucity of paediatric data. Protocols are less well developed in preschool asthma, where steroid insensitive disease is much more common, but the use of two simple measurements, aeroallergen sensitisation and peripheral blood eosinophil count, allow the targeted use of inhaled corticosteroids. There is also increasing evidence that chronic airway infection may be important in preschool wheeze, raising the possibility that targeted antibiotics may be beneficial. Asthma in the first year of lfe is not driven by Type 2 inflammation, so beyond avoiding prescribing inhaled corticosteroids, no evidence based recommendations can be made. In the future, we urgently need to develop objective biomarkers, especially of risk, so that treatment can be targeted effectively; we need to address the scandal of the lack of data in children compared with adults, precluding making evidence-based therapeutic decisions; and move from guiding treatment by phenotypes, which will change as the environment changes, to endotype based therapy.